MIND THE GAP: THE POTENTIAL OF PROFESSIONAL YOUTH WORK FOR CIVIC EMPOWERMENT AND ENGAGEMENT OF YOUTH AT SOCIAL RISK - Ronald Crouzé; Tom Vanwing; Pieter Meurs (Journal of Social Intervention: Theory and Practice, 2022)
Youth work is often regarded as a fruitful place for the creation of democratic citizens and is thus a favoured space for civic educational activities. Despite these efforts, there is a growing concern on the civic empowerment gap: the difference that can still be found across various domains of civic outcomes between disadvantaged groups and those from dominant and socio-economically advantaged backgrounds. From a democratic point of view, the civic empowerment gap is deeply problematic. Various efforts exist to include excluded or so-called ‘nonparticipating’ youngsters, albeit often with a socialization or disciplinarian discourse. The presented study challenges such approach and builds on the concept of political subjectification to offer an alternative approach to remedy the civic empowerment gap? To do so, a case study has been conducted with a youth social organization in Molenbeek, Brussels. The findings emphasize the importance of the explicit and implicit role of advocacy by the organization and the importance of the fragile pedagogical and political relationship between youth workers and youngsters to enable meaningful participation.